2003
DOI: 10.1089/08927790360587414
|View full text |Cite
|
Sign up to set email alerts
|

Photoselective Vaporization of the Prostate: Initial Experience with a New 80 W KTP Laser for the Treatment of Benign Prostatic Hyperplasia

Abstract: This pilot study indicates that PVP with the new 80 W KTP/532 laser is a simple, safe, and efficacious outpatient procedure for the treatment of obstructive BPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(73 citation statements)
references
References 10 publications
1
69
0
3
Order By: Relevance
“…Recent studies showed reduced blood loss and avoidance of TUR syndrome even in high-risk patients [10][11][12]. Thus, the objective of the present study was to use the Greenlight system for treating of BPH in prostates of ≥ 80 mL, and to investigate the safety and outcome of this procedure, comparing it with results from Greenlight therapy for smaller prostates of < 80 mL.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed reduced blood loss and avoidance of TUR syndrome even in high-risk patients [10][11][12]. Thus, the objective of the present study was to use the Greenlight system for treating of BPH in prostates of ≥ 80 mL, and to investigate the safety and outcome of this procedure, comparing it with results from Greenlight therapy for smaller prostates of < 80 mL.…”
Section: Introductionmentioning
confidence: 99%
“…Although effective, the technique can be associated with significant complications, including TUR syndrome and bleeding [3][4][5][6]. Newer technologies such as PVP offer safer and equally effective alternatives to relieve symptomatic bladder outlet obstruction [7][8][9][10][11][12][13][14][15]. Few studies however have directly examined the clinical differences between 80 W vs. 120 W PVP [17].…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been shown to result in comparatively fewer complications, e.g. reduced incidence of TUR syndrome as well as bleeding [7][8][9][10][11][12][13][14][15], Improvements to the Greenlight ™ laser system have been made over time, particularly with the introduction of the 120 W HPS system in 2006. Few however have compared the clinical performance of the newer systems with their predecessors.…”
Section: Introductionmentioning
confidence: 99%
“…The first use of an 80-W KTP laser on humans was reported by Hai and Malek in 2003 [10]. Since then, the efficacy and safety of highpower KTP laser vaporization has been demonstrated in multiple trials.…”
Section: Discussionmentioning
confidence: 99%